Chitosan/clay films' properties as affected by biopolymer and clay micro/nanoparticles' concentrations - Casariego, A. (2009)
Blends of chitosan (from Cuban lobster) and clay micro/nanoparticles were prepared by dispersion of the clay particles in the film matrix and the films obtained were characterized in terms of water solubility, water vapor, oxygen and carbon dioxide permeability, optical, mechanical and thermal properties using an Instron universal testing machine, differential scanning calorimetry, thermogravimetric analyses and scanning electron microscopy (SEM). The water vapor barrier properties of the films were significantly improved by incorporation of clay in their composition, while the water solubility decreased as the clay concentration increased (for a constant chitosan concentration). The tensile strength of chitosan/clay films increased significantly with increasing chitosan and clay concentrations, while the values of elongation decreased slightly for high values of chitosan concentration. Tm increased with the increase of chitosan concentration, but the changes in Tm with the addition of clay were not significant. Polynomial models were fitted to the experimental data in order to facilitate future design of chitosan/clay film systems.